Corrosion resistance of steel coated with different coating systems, containing HAA-polyester powder coating as a top layer - Lazić Dragana; Dimitrijević Marko; Stupar Stevan; Bučko Mihael (Scientific Technical Review)
This study aimed to assess the impact of surface geometry, preparation, and coating procedures on the corrosion behavior of HAA-polyester powder coated steel components in a salt spray test. The coating process of the steel parts involved degreasing, Zn spray coating, an epoxy powder primer, and a polyester powder topcoat. Results highlighted the crucial role of surface geometry, with flat surfaces showing superior corrosion resistance compared to welded joints, sharp edges, or hollow cylinders. For standard flat panels, no red rust was observed for over 600 hours in the salt chamber, meeting ISO 12944-6 requirements. However, non-standard panels with complex geometries showed rust much earlier, particularly after 108 hours in welded zones and sharp corners when an epoxy primer was not used. Applying the primer extended corrosion resistance by 2-3 times. Hollow cylinders developed rust after 240 hours due to insufficient coating thickness inside the cylinders. Crevices remained vulnerable, as the coating did not reach inner parts. Applying powder to individual components before assembly, and using brush painting on critical areas, such as welded joints and sharp corners, are strongly suggested to improve protection. Additionally, the evaluated polyester powder coatings exhibited outstanding mechanical strength and camouflage capabilities, making them highly suitable for military applications.